小児シェーグレン症候群の1例 - 比嘉, 努; 狩野, 岳史; 澤田, 茂樹; 新垣, 敬一; 石橋, 佳奈; 比嘉, 桂子 (日本口腔外科学会雑誌, 2019)
Sjjögren’s syndrome (SS) is a chronic autoimmune disease characterized by a progressive lymphocytic infection of the exocrine gland with varying degrees of systemic involvement. SS is thought to be rare in childhood. However, a recent epidemiological study revealed that the incidence of childhood SS per 100,000 children was more than 0.5. Here we report a case of SS in childhood. A 14-year old girl presented with a rash on her forearm and cheek, but did not complain of dry mouth. Salivary secretion was decreased, and moisture value was measured at the dry mouth level. Ultrasonography revealed multiple hypoechoic areas, hyperechoic bands, and a reticular pattern on salivary glands. On laboratory examinations, antinuclear antibody, anti Ro/SS-A antibody, and anti-La/SS-B antibody were positive. The histopathological finding in the minor salivary gland was chronic inflammation. A diagnosis of SS was made from these findings. We summarized previous reports on child patients with SS and compared it with clinical features in adult patients. Children with SS complain frequently of rash and fever, but rarely of a dry mouth.